Learning Design for Translation Concepts Using Bola Kasti Games - Mariela, Anadia Muli; Zulkardi, Zulkardi; Susanti, Ely; Meryansumayeka, Meryansumayeka (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Students often struggle to grasp geometric transformation concepts, particularly translation. Although some students can recognize object movement visually, conceptual misconceptions persist in interpreting the meaning of displacement, along with difficulties in representing movement visually using Cartesian diagrams. This condition indicates the need for a more contextually and meaningfully grounded learning approach that connects mathematical concepts with activities familiar to students. In this study, the traditional game of bola kasti is employed as an effective learning medium, serving as a cultural activity that is relevant and closely related to students’ experiences. The traditional bola kasti game functions not merely as a contextual illustration but is systematically designed as a conceptual transition tool that bridges physical activities and formal coordinate representations in the concept of translation. This research aims to develop a learning trajectory using the PMRI approach, incorporating the context of the bola kasti game to support students in constructing a deep understanding of the concept of translation. The research employed a design research methodology with a validation study type, involving 32 ninth-grade students from SMP Negeri 52 Palembang. Data collection techniques included student activity sheets, classroom observations, and interviews, which were analyzed descriptively using a qualitative approach. The findings indicate that the Actual Learning Trajectory (ALT) aligns with the designed Hypothetical Learning Trajectory (HLT). Therefore, the developed HLT is considered successful and contributes to the development of a Local Instructional Theory (LIT) in enhancing students’ conceptual understanding progressively, as demonstrated by students’ ability to identify the direction and magnitude of translation and to represent translations using Cartesian diagrams through the PMRI approach with the context of the bola kasti game in translation learning.